intrínseco Phonological primes of extrinsic timing vs. phonological primes of intrinsic timing - Adelaide Hercília Pescatori Silva (Fórum Linguístico, 2008)
This paper aims at presenting and discussing the distinction established between phonological models of intrinsic timing control and phonological models of extrinsic timing control. Based on phonetic data reported by the literature, especially the ones concerning coarticulation and gradient allophonies, we argue that the only way of dealing satisfactorily with such phenomena is considering "time" to be intrinsic to the structure of the unit of analisis. This representation that incorporates "time" to the prime structure is necessary because many of the reported facts concerning coarticulation and gradient allophonies are conditioned by the prosodic structure of the languages.